(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article covers in detail modern approaches to complex diagnostics and correction of mental development disorders in children with cerebral palsy (CP). It is shown that mental disorders in CP are diverse and are represented by cognitive disorders (impaired perception, memory, attention, visual-motor coordination, intelligence and speech), residual organic borderline disorders (cerebrosthenic, neurosis-like, psychopathic syndromes), as well as pathological personality development (character accentuation, mental infantilism). Diagnostics of mental disorders in CP is a complex task due to their diverse combination with motor, speech and sensory pathology, which requires an integrated approach. The article describes differential diagnostic criteria for distinguishing between mental retardation and intellectual disability in cerebral palsy, and also covers in detail modern trends in comprehensive rehabilitation (including medical, social, psychological and pedagogical correction) of cognitive, emotional and behavioral disorders in patients with cerebral palsy